Beneficial Alteration in Growth Performance, Immune Status, and Intestinal Microbiota by Supplementation of Activated Charcoal-Herb Extractum Complex in Broilers - Wang, Lixue; Zhang, Ying; Guo, Xiangyue; Gong, Limin; Dong, Bing (Frontiers in Microbiology, 2022)
This study aimed to examine the effects of activated charcoal-herb extractum complex (CHC) on the growth performance of broilers, inflammatory status, microbiota, and their relationships. A total of 864 1-day-old Arbor Acres male broilers (41.83 ± 0.64 g) were distributed to eight dietary treatments with six replicates (18 birds per replicate), which were a corn-soybean meal-based diet (NCON); basal diets supplemented with 250, 500, 750, or 1,000 mg/kg CHC, and three positive controls; basal diets supplemented with 200 mg/kg antibacterial peptide (AMP), 200 mg/kg calsporin (Probio) or 500 mg/kg montmorillonite. The study period was 42 days including the starter (day 0–21) and grower (day 22–42) phases. Compared with the NCON group, CHC supplementation (optimal dose of 500 mg/kg) increased (p < 0.05) growth performance and tended to increase feed conversion rate in broilers. CHC (optimal dose of 500 mg/kg) decreased the level of the interleukin-1β (IL-1β) and interferon-γ (IFN-γ) in serum and improved the levels of immunoglobulins A (IgA) and immunoglobulins A (IgM) in serum, and secretory immunoglobulin A (SIgA) in the mucosa of duodenum and jejunum (p < 0.05). In the ileum, CHC supplementation decreased community abundance represented by lower Sobs, Chao 1, Ace, and Shannon compared with NCON (p < 0.05). At the phylum level, CHC supplementation increased the abundance of Firmicutes, while decreasing the abundance of Bacteroidetes in ileum and cecum (p < 0.05). At the genus level, compared with the NCON group, CHC markedly reduced (p < 0.05) the abundances of pathogenic bacteria Alistipes in the ileum, which were negatively associated with the levels of SIgA and IL-1β in ileum mucosa. In conclusion, CHC had beneficial effects on growth performance, immune status, and intestinal microbiota composition. CHC had dual functions of absorption like clays and antibacterial like antibacterial peptides.